1999
DOI: 10.2466/pms.1999.89.1.223
|View full text |Cite
|
Sign up to set email alerts
|

Learning Volleyball Serves: A Preliminary Study of the Effects of Knowledge of Performance and of Results

Abstract: Recently, doubts have begun to surface about the emphasis that for years has been given to the variable knowledge of results in motor learning, and a view has been expressed that information on how an action has been made (knowledge of performance) may be of more use. This study compared the two types of information in learning a volleyball serve by eight subjects, who were given the two kinds of feedback at various points in the process. Analysis seems to show that knowledge of performance tends to be more ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 14 publications
1
7
0
2
Order By: Relevance
“…However the within–group comparison of the KP group also showed there was a significant improvement at the end of the program. This finding could be in agreement with the study results of Zubiaur M et al 26 ) , who stated that knowledge of performance tends to be an effective mode of intervention for learning.…”
Section: Discussionsupporting
confidence: 93%
“…However the within–group comparison of the KP group also showed there was a significant improvement at the end of the program. This finding could be in agreement with the study results of Zubiaur M et al 26 ) , who stated that knowledge of performance tends to be an effective mode of intervention for learning.…”
Section: Discussionsupporting
confidence: 93%
“…KP is information about movement characteristics that led to the performance [ 80 ]. Both kinds of feedback are valuable [ 102 , 104 , 105 ], although there is some evidence that, for skill learning in general [ 106 , 107 ]and also specifically for persons after stroke [ 108 ], the use of KP during repetitive movement practice results in better motor outcomes. Van Dijk et al [ 109 ] performed a systematic literature search to assess effectiveness of augmented feedback (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The present findings may speak to the effects of knowledge of performance feedback often provided by teachers and coaches during practice. Previous research has shown that knowledge of performance feedback effectively increases practice performance and performance following practice when compared to other forms of feedback (Sharma, Chevidikunnan, Khan, & Gaowgzeh, 2016;Wallace & Hagler, 1979;Zubiaur, Ona & Delgado, 1999). When describing the kinematic features of movements to learners, increasing levels of self-awareness of the activity may be one consequence of that form of extrinsic feedback.…”
Section: Discussionmentioning
confidence: 99%